A programmable powerful and ultra-fast water-driven soft actuator inspired by the mutable collagenous tissue of the sea cucumber. Issue 29 (29th June 2021) - Choi, Andrew; Han, Hyeonseok; Kim, Dong Sung
Abstract : Composition/dimensional adjustment of a bulk PNIPAAm-based water-driven soft actuator tuned actuation force/speed in wide ranges at maximum of 2 N and 3 s −1, respectively, demonstrating immediate potentials in soft robotics and biomedical appliance. Abstract : The sea cucumber evolved to bear mutable collagenous tissue (MCT) that enables its elastic modulus to change by a factor of 10 within a few seconds. It does this by controlling the amount of chemical regulator released, which can subsequently form or break hydrogen bonds within the MCT. Although existing water-driven, self-operating, soft actuators have great potential for soft robotics, they remain fragile and slow; ergo, their range of application remains modest. Inspired by MCT, we introduce a programmable, powerful, and ultra-fast water-driven self-operating soft actuator exerting an actuation force of approximately 2 N with an actuation speed of approximately 3 s −1 in 80 °C water based on the dramatic stiffness alteration of bulk poly( N -isopropylacrylamide) hydrogel. This actuator also exhibits outstanding robustness by preserving its original shape over multiple cycles of highly strained (300%) actuations under harsh environments. A simple modulation of cross-linker concentration with its dimensional adjustment enabled the precise tuning of not only the actuation force but also the actuation speed in a wide range. Thus, the soft robotic gripper was able to perform a myriad of intricate tasks such as capturing a fragile object, acting as a biomedical appliance, and closing a large wound with uniform appropriate forces.